Becoming the Pastor You Hope to Be: Four Practices for Improving Ministry - Blodgett, Barbara J. (Rowman & Littlefield Publishers, 2011)
Becoming the Pastor You Hope to Be unapologetically urges clergy readers to develop practices that will help them become more excellent ministers. A long-time field educator, now serving as a denominational staff person responsible for ministerial formation, Barbara Blodgett believes excellence is a matter of doing simple things with care and consistency. Ministers who commit themselves to excellence will grow and flourish, and even become happier in ministry. Blodgett urges ministers to resist praise and instead to ask for feedback, to seek the company of mentors who are better than the reader is at what he or she does, to be vulnerable before their peers in order to learn from them, and to define themselves as a leader who does not merely take activist stances but risks entering into deep, transformative relationships. Improvement in ministry, Blodgett argues, comes about not through extraordinary leaps and bounds but rather through adoptingsimple habits and carrying through on small but thoughtfully made choices. Addressed to ministers, ecoming the Pastor You Hope to Be is also a valuable resource for discernment committees, Christian educators, leaders of continuing education and lay education programs, and all those who partner with theological schools to help form ministers, both lay and ordained.